How classroom physical and environmental conditions influence students´ attitudes and perceptions within the english language classroom - Palacios Molina, Alex Danilo
One way to reflect learning is through students´ attitude in class. Learning happens in different settings. Since long time ago the learning process has been developed in a classroom which may be a great environment to provide the stimuli needed to help a student develop his/her potential (Vekata 2010). The classroom is expected to be an environment conductive to learning, since learning requires a reasonable level of concentration in listening, writing, and reading. Research on classroom environment has shown that the physical arrangement can affect the behavior of both students and teachers and that a well structured classroom tends to improve students’ academic and behavioral outcomes (Hoffman 2004). Higgins et al (2005) provides a definition of these physical conditions of the classroom as seating, furnishings, spatial density, privacy, noise and acoustic, climate and air quality, and lights.